التفكير الناقد عند علماء الحديث (Critical Thinking of Hadith Scholars) - محمد, سعد الدين منصور; العباس, تاج الدين أحمد سعيد (Journal of Islam in Asia (E-ISSN 2289-8077), 2018)
الملخّص هذا البحث تناول معنى التفكير الناقد من خلال تتبع مناهج أهل الحديث، بعد التعريف به وبيانه لغةً واصطلاحاً، حيث أشار البحث إلى مناهج المحدثين ونقدهم للسند والمتن الذى يتكون منه الحديث، بجانب نظرتهم الثاقبة حتى يصلوا إلى تصحيح الحديث أو تحسينه أو تضعيفه والحكم عليه من خلال دراسة سند الحديث ورجاله، إذا أنه الطريق الموصل لمتن الحديث، حيث كانت هناك طبقات ثلاثة عرفت عند المحدثين بالتشدد والاعتدال والتساهل، من حيث الحكم على الرواة جرحاً وتعديلاً، وألفت في ذلك جملة من كتب الرجال شملت الثقات والضعفاء والكتب التى جمعت بينهما، بجانب ذلك أهتم أهل الحديث بنقد المتون، وذلك بالنظر في متن الحديث، وجمع طرقه والنظر إلى علله، حتى يصلوا إلى الحكم على الحديث، والآن هذه المناهج صارت تدرس كمواد تخصصية لطلاب الحديث، والمنهج المتبع هو المنهج الاستقرائي والتحليلي، ووصل البحث إلى نتائج دلت على وجود التفكير النقدي عند أهل الحديث وتطبيقهم له. الكلمات المفتاحية: التفكير، النقد، مناهج، المحدثين، متن، سند. Abstract This research after literal and technical definition looks into the meaning of critical thinking within the methodology of Hadith scholars. This research discusses the methods of Hadith scholars in critically examining the chain of transmitters (sanad) and the hadith text (matn) itself beside their shrewd insights and ability to scrutinize hadith as authentic (taṣÍÊÍ), good (taÍsÊn), or weak (taḍʿÊf). In relation to evaluating hadith through studying its chain and its transmitters that eventually leads to the hadith text, there are three categories of evaluators known to the hadith scholars as rigid (tashaddud), moderate (iʿtidÉl) and lenient (tasÉhul). As far as the critical evaluation of the transmitters are concerned, there are ample number of biographical works (kutub al-rijÉl) written on the trustful narrators (al-thiqqÉt) and on the weak narrators (al-ḍuʿafÉ’) while some works compiled both types of narrators in one book. Adding onto this, the Hadith scholars were also interested in scrutinizing Hadith through its texts by studying all its variations and its contexts in order to evaluate the status of the hadith. Presently, these methods are being taught as subjects of specialization for the Hadith students. Using inductive and analytical methods this work finds that there is a form of critical thinking in Hadith methodology employed by the Hadith scholars. Key words: Thinking, critique, methods, Hadith scholars, Hadith methodology, Hadith text (matn), Hadith Chain (sanad).